ANALYSIS OF PUBLIC SERVICE SKILLS IN THE OPERATION OF ELECTRONIC MEDICAL RECORDS (EMR) AT M.M. DUNDA LIMBOTO REGIONAL GENERAL HOSPITAL (RSUD) - Hartati Inaku; Ansar, Yanti Aneta, Udin Hamim (Adisam Publisher, 2025)
This study analyzes the professionalism and service skills related to Electronic Medical Records (EMR) at M.M Dunda Limboto Regional General Hospital (RSUD). Research data were collected through interviews, observations, and documentation and analyzed using an interactive model analysis method consisting of data collection, data presentation, data reduction, data verification, and conclusion drawing. The results indicate that the skills of public service officers in operating EMRs remain inadequate. This is primarily due to the absence of personnel with an educational background in information technology (IT) at RSUD M.M Dunda Limboto. Consequently, the hospital relies on its existing staff and provides them with technical training (Diklat Teknis) on EMR usage. However, the training only covers procedural aspects of EMR operation without equipping staff with the necessary knowledge to handle technical disruptions. Consequently, public services based on EMR remain ineffective and cannot be considered optimal.